2021
DOI: 10.1155/2021/6648009
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Algorithm for Demand Forecast Analysis on Flash Sales Platform

Abstract: With the development of the digital economy, the emerging marketing strategy of the e-commerce flash sales has been changing the traditional purchasing habits of customers. This imposes new decision-making challenges for companies involved in flash sales. It is important for companies to build the accurate product demand forecast analysis focusing on the characteristics of the flash sales and customer behaviors. In this paper, VIPS (Weipinhui, a Chinese e-commerce platform) is taken as a case study with the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…At this stage, information search and online comments have become the focus of attention, which can be matched to consumers' potential search needs in marketing (Attia et al, 2023). M. Zhang et al (2021) aimed at the problem of poor recommendation quality in the case of sparse data, and this paper proposes a recommendation algorithm for sparse data by optimizing the filling of scoring vacancies and considering the number of common scoring items. The effect of the model is more obvious with the increase of data sparsity (M. Zhang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, information search and online comments have become the focus of attention, which can be matched to consumers' potential search needs in marketing (Attia et al, 2023). M. Zhang et al (2021) aimed at the problem of poor recommendation quality in the case of sparse data, and this paper proposes a recommendation algorithm for sparse data by optimizing the filling of scoring vacancies and considering the number of common scoring items. The effect of the model is more obvious with the increase of data sparsity (M. Zhang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…M. Zhang et al (2021) aimed at the problem of poor recommendation quality in the case of sparse data, and this paper proposes a recommendation algorithm for sparse data by optimizing the filling of scoring vacancies and considering the number of common scoring items. The effect of the model is more obvious with the increase of data sparsity (M. Zhang et al, 2021). showed that, with the popularization of social media, the content in social networks has increased dramatically, and recommendation systems have attracted considerable attention.…”
Section: Literature Reviewmentioning
confidence: 99%